ANALISIS KEBUTUHAN BAHAN AJAR BAHASA INGGRIS DENGAN METODE TOTAL PHYSICAL RESPONSE (TPR) BERBASIS PENDIDIKAN KARAKTER DI SEKOLAH DASAR - Antika, Rindilla; Syari, Elsy Melia (Sekolah Tinggi Keguruan dan Ilmu Pendidikan Nasional, 2022)
This study aims to describe English teaching materials and identify the needs of English language teaching materials based on character education by using the Total Physical Response (TPR) method at SDIT Mutiara Bunda Kota Pariaman. This research is a Research Development (R and D) with qualitative descriptive research design. Participants of this study were teachers and students of grade V SDIT Mutiara Bunda Kota Pariaman. Instruments of this research are questionnaires, interviews, and observations. The results showed that teachers and students needed English-based teaching materials based on character education. The teaching material needed is a teaching material that is easy to understand and comprehend and it can be used by teachers and students. In addition, the teaching materials are also able to make students active, creative, and communicative. Moreover, the attitude the students wants are a confident attitude, responsibility, and love to to work hard. Thus, it can be concluded that English teaching materials need to be developed using Total Physical Response (TPR) method based on character education